2006
DOI: 10.5194/angeo-24-1469-2006
|View full text |Cite
|
Sign up to set email alerts
|

Top-side ionosphere response to extreme solar events

Abstract: Abstract. Strong X-flares and solar energetic particle (SEP) fluxes are considered as sources of topside ionospheric disturbances observed by the ROCSAT-1/IPEI instrument during the Bastille Day event on 14 July 2000 and the Halloween event on 28 October-4 November 2003. It was found that within a prestorm period in the dayside ionosphere at altitudes of ∼600 km the ion density increased up to ∼80% in response to flare-associated enhancements of the solar X-ray emission. Ionospheric response to the SEP events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Many serious events (e.g. the 1989 events, the 2000 Bastille Day event, the October-November 2003 storms [81], and the 1859 event [82]) have been reported in the literature. Although there are innumerable case studies and statistical studies on ionospheric storms, it remains difficult to reliably predict the accurate evolution of the ionosphere when a serious solar event erupts.…”
Section: The Ionosphere Under Extreme Solar Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many serious events (e.g. the 1989 events, the 2000 Bastille Day event, the October-November 2003 storms [81], and the 1859 event [82]) have been reported in the literature. Although there are innumerable case studies and statistical studies on ionospheric storms, it remains difficult to reliably predict the accurate evolution of the ionosphere when a serious solar event erupts.…”
Section: The Ionosphere Under Extreme Solar Conditionsmentioning
confidence: 99%
“…Solar energetic particles (SEPs) also anomalously erupt and accompany solar flares, and are termed solar proton events [81,83]. The SEP and X-ray effects overlap in the sunlit hemisphere.…”
Section: Response Of the Ionosphere To Solar Flaresmentioning
confidence: 99%
“…This study emphasized the importance of the spectra of solar flares for SFEs. Dmitriev et al [2006] studied the response of the ionosphere to X‐ray emissions and solar energetic particles during the above solar flares. Sahai et al [2006] noted unusual Brazilian sector ionospheric effects associated with the 28 October flare.…”
Section: Introductionmentioning
confidence: 99%
“…Supposing the relativistic SEP spectral index of 1.5 during the flare (Dmitriev et al, 2006;Wang and Wang, 2006), we obtain the 41 GeV proton energy flux of $9 Â 10 À6 W m À2 . That flux is $30 times smaller than the energy flux of X-rays in the maximum of Halloween GLE.…”
Section: Article In Pressmentioning
confidence: 99%
“…On the other hand, for extremely strong solar flares on July 14, 2000 and October 28, 2003 it has been found that the duration of TEC enhancements is longer on tens of minutes than the duration of flares in EUV and X-rays (Liu et al, 2004;Tsurutani et al, 2005). Dmitriev et al (2006) demonstrate that during those flares the ionospheric ionization is additionally contributed by the SEP, which can produce long-lasting ion density enhancements right after the X-ray flares.…”
mentioning
confidence: 95%